ЕСКИ ҚЫПШАҚ ЕСТЕЛИГИ – «КИТАБ АТ-ТУҲФАТ УЗ-ЗАКИЙЙА ФИЛ-ЛУҒАТ-ИТ-ТУРКИЙА» МИЙНЕТИ - Абдиназимов, Ш.Н. (ILIM hám JÁMIYET, 2025)
The article presents information about one of the written monuments of the Kipchak language of the 13th-15th centuries – the monument "Kitab at-tukhfat uz-zakiya fil-lugat at-Turkiya". The circumstances of the monument’s research were analyzed. The dictionary and grammar sections of the monument are mentioned.